Efficient nitrogen removal and recovery from real digested sewage sludge reject water through electroconcentration. Issue 5 (October 2021) - Koskue, Veera; Freguia, Stefano; Ledezma, Pablo; Kokko, Marika
Abstract: Reject waters from the dewatering of anaerobically digested municipal sewage sludge are nitrogen-rich (ca. 1 gNH4-N L −1 ) wastewater streams. They account for up to 25% of the total nitrogen load of wastewater treatment due to their internal recirculation within treatment plants. In this study, nitrogen was effectively removed and recovered from real reject water using a novel electrochemical setup combining electroconcentration and stripping. High nitrogen removal (≤ 94 ± 0.7%) and recovery (≤ 87 ± 8.5%) efficiencies from real reject water were obtained while simultaneously reducing the influent nitrogen concentration of 913 ± 14 mgNH4-N L −1 to 57 ± 6.7 mgNH4-N L −1 in the effluent. Most of the nitrogen recovery took place via electroconcentration into a liquid concentrate (≤ 82 ± 5.7%), while stripping contributed little to the removal and recovery (≤ 5 ± 2.8%). The reported removal and recovery efficiencies are the highest to date for a system utilising three-chamber electroconcentration. Furthermore, the concept of cation load ratio (the ratio between applied current density and cation loading rate) was introduced as a more precise parameter than the widely used and simpler NH4 -N load ratio for predicting the performance of a (bio)electrochemical nutrient removal and recovery system. Graphical Abstract: ga1 Highlights: Nitrogen removal and recovery from real reject water were extensively studied. Up to 94% of nitrogen was electrochemically removed from a real reject water stream. Nitrogen was effectively recovered (up to 82%) into a liquid concentrate. Stripping contributed to less than 5% to nitrogen removal and recovery. Low effluent nitrogen concentrations can remove the need for additional treatment.